2019
DOI: 10.1021/acs.est.9b02890
|View full text |Cite|
|
Sign up to set email alerts
|

Transport and Redistribution of Radiocesium in Fukushima Fallout through Rivers

Abstract: The Fukushima Daiichi Nuclear Power Plant (FDNPP) accident released the most significant quantity of radiocesium into the environment since Chernobyl, and detailed measurements over the initial 5 years provide new insights into fluvial redistribution of radiocesium. We found that the high initial activity concentration of 137Cs-bearing suspended sediment in rivers was followed by a steep exponential decline (λ1) which extended to approximately 1 year after the accident, while the rate of initial decline in rad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
62
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 103 publications
(65 citation statements)
references
References 46 publications
3
62
0
Order By: Relevance
“…In fields covered with sufficient vegetation, the discharge rate of radiocesium is low, whereas that in the fields with small plants is relatively high. In some test fields, it was observed that radiocesium discharge rate was drastically pro-moted by weeding, and cultivation tends to accelerate radiocesium migration; in particular, soil puddling before rice planting has played an important role in discharging radioceisum deposited in paddy fields [50]. Therefore, the discharge of radiocesium from farmland contributes significantly to migration of radiocesium at a large scale as discussed next.…”
Section: Deposited Radionuclidesmentioning
confidence: 94%
See 4 more Smart Citations
“…In fields covered with sufficient vegetation, the discharge rate of radiocesium is low, whereas that in the fields with small plants is relatively high. In some test fields, it was observed that radiocesium discharge rate was drastically pro-moted by weeding, and cultivation tends to accelerate radiocesium migration; in particular, soil puddling before rice planting has played an important role in discharging radioceisum deposited in paddy fields [50]. Therefore, the discharge of radiocesium from farmland contributes significantly to migration of radiocesium at a large scale as discussed next.…”
Section: Deposited Radionuclidesmentioning
confidence: 94%
“…The decreasing tendency of radiocesium concentration in rivers was faster than that observed in the Chernobyl accident, and this is considered to have been due to the difference in environmental conditions [50]. Areas surrounding Chernobyl are dominated by fields and forests, whereas those surrounding the Fukushima NPP include urban and farmland (with paddies).…”
Section: Deposited Radionuclidesmentioning
confidence: 95%
See 3 more Smart Citations